The Volatility of Capital Flows in Emerging Markets : Measures and Determinants - Sole Pagliari, Maria; Hannan, Swarnali (Washington, D.C. : International Monetary Fund, 2017)
Capital flow volatility is a concern for macroeconomic and financial stability. Nonetheless, literature is scarce in this topic. Our paper sheds light on this issue in two dimensions. First, using quarterly data for 65 countries over the period 1970Q1-2016Q1, we construct three measures of volatility, for total capital flows and key instruments. Second, we perform panel regressions to understand the determinants of volatility. The measures show that the volatility of all instruments is prone to bouts, rising sharply during global shocks like the taper tantrum episode. Capital flow volatility thus remains a challenge for policy makers. The regression results suggest that push factors can be more important than pull factors in explaining volatility, illustrating that the characteristics of volatility can be different from those of the flows levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet